Monitoring road safety in an information-wired environment: the case of Piedmont - Sylvie Occelli (Netcom)
Today, Information and Communication Technologies (ICTs) are an essential determinant of urban change. They make it possible to build new Socio-Technical Systems (STS) where the knowledge flow initiated by the interactions of ICT-enabled nodes has a crucial role. This contribution illustrates examples of these systems. Reference is made to the Piedmont Region, where a socio-technical system had to be established in order to support the monitoring of the regional road safety policy. The contribution is divided into two main parts. First, insights for developing the STS are given and an overview of the road safety planning issues in Piedmont is presented; there then follows a description of the STS and an account of its regional application and installation.